Empowering smart customer to participate in electricity supply system: Extended of technology acceptance model - Fairus , Abu; Ahmad Rozelan, Yunus; Izaidin, Abdul Majid; Juhaini, Jabar; Amir, Aris; Hamzah , Sakidin (Penerbit UTeM, 2014)
Based on the literature on the technology acceptance model (TAM) and related efforts in technology adoption research, this paper proposed an extended model for analyzing supply system acceptance of users. Innovation adoption has been widely researched in academe, industry and the public sector. The user readiness to adopt and use smart grid will be evaluates using Technology Acceptance Model. This literature review is based on articles relating to TAM model being identified and observed to have been published in journals from databases EBSCOhost , Emerald, Proquest New Platform, Science Direct and IEEE Explore between the year 1998-2013. The most recent studies investigate the TAM model in information system and involved service industries in its scope have been reviewed. A discussion on the TAM model and factor on consumer acceptance smart grid is presented and conceptual framework and model are proposed.